HUKUM PERLINDUNGAN KONSUMEN TERHADAP DATA PRIBADI DI ERA E-COMMERCE - NIM. A1011211264, AFIF FADHIL FADHULLAH (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Transaction activities carried out in e-commerce in their implementation must be in accordance with positive legal regulations in Indonesia, specifically regulated in Law Number 8 of 1999 concerning Consumer Protection, Article 4 Point 1 of Law Number 8 of 1999 concerning Consumer Protection which explains that consumers have the right to comfort, security, and safety in consuming goods or services. Article 26 paragraph (1) of Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions also states that the use of any information through electronic data concerning a person's personal data must be carried out with the consent of the person concerned. Therefore, business actors in this case are required to provide comfort, security and safety to consumers in consuming goods or services through e-commerce facilities. The form of the formulation of the problem that underlies this research is as follows: